Conveying environmental harms through music: some directions for green-cultural criminology - Ronco, Anna Di (Criminological connections, directions, horizons, 2025)
This chapter contributes to the perspective of green-cultural criminology, which was pioneered by Nigel South and Avi Brisman with an agenda-setting article and a book published ten years ago (Brisman and South, 2013, 2014). Drawing on our previous work in Italy on the criminalised NoTap eco-justice movement and the environmental disaster of Casale Monferrato, we aimed to show how green-cultural criminology can extend its study of representations of environmental harms to music, as the latter can be an important conveyor of harms and resistance while also being a powerful healing tool. We conclude our tribute to a great scholar, friend and music lover with a coda-conclusion where we reinforce the need to study music within green-cultural criminology, also identifying directions for future research in this area.